The phase-polarization curve of asteroid (3200) Phaethon†. Issue 3 (30th June 2018) - Devogèle, M; Cellino, A; Borisov, G; Bendjoya, Ph; Rivet, J-P; Abe, L; Bagnulo, S; Christou, A; Vernet, D; Donchev, Z; Belskaya, I; Bonev, T; et al.
ABSTRACT: A multicolour phase-polarization curve of asteroid (3200) Phaethon has been obtained during the 2017 December apparition by merging measurements taken at the observing station of Calern (France) and at the Rozhen observatory (Bulgaria). All the observations were obtained in the positive polarization branch, the phase angle ranging from 36° to 116°. The measured values of linear polarization are among the highest ever observed for a Solar system body. The covered interval of phase angle was not sufficiently extended to derive a firm determination of the P max parameter, but this appears to occur at a phase angle around 130° and reaches more than 45 per cent of linear polarization. Phaethon is the parent body of the Geminid meteor shower, and the real physical nature of this object (asteroid or comet) has been a long-debated subject. Our polarimetric measurements seem to support the asteroid hypothesis with a phase-polarization curve similar to the asteroid (2) Pallas, but further observations at smaller phase angles are needed to draw definitive conclusions.